2018
DOI: 10.1590/2177-6709.23.5.39.e1-13.onl
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between tooth size-arch length discrepancy and interradicular distances measured on CBCT and panoramic radiograph: an evaluation for miniscrew insertion

Abstract: Introduction: The selection of appropriate sites for miniscrew insertion is critical for clinical success. Objectives: The aim of the present study was to evaluate how interradicular spaces measured on panoramic radiograph compare with Cone-Beam Computed Tomography (CBCT), and how crowding can influence the presence of available space for miniscrew insertion, in order to define a new “safe zones” map. Methods: A total of 80 pre-treatment panoramic radiographs and 80 CBCT scans with corresponding digital models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 38 publications
(26 reference statements)
1
24
0
11
Order By: Relevance
“…When determining the best location for placing miniscrews, panoramic radiographs can underestimate the available interdental bone space 30 . The accuracy of periapical radiographs is greater than that of panoramic radiographs when assessing the length of the tooth roots 31 and when determining the position of mini-implants 32 .…”
Section: Discussionmentioning
confidence: 99%
“…When determining the best location for placing miniscrews, panoramic radiographs can underestimate the available interdental bone space 30 . The accuracy of periapical radiographs is greater than that of panoramic radiographs when assessing the length of the tooth roots 31 and when determining the position of mini-implants 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the stability of the micro-screw can be influenced by the choice of the implantation site, the bone condition at the implant site and the distance from the adjacent teeth. The application of CBCT will increase the accuracy of implantations and reduce the failure rate [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Uma das possibilidades existentes, se trata da utilização dos implantes dentários ósseo-integrados, os quais são capazes de oferecer uma ancoragem confiável e a movimentação dentária, contudo, devido ao seu tamanho, suas utilizações se tornaram limitadas (ROBERTS et al, 1996). Como o próprio nome diz, esses acessórios foram projetados para serem inseridos no osso alveolar, de forma temporária (TEPEDINO et al, 2018). Sua utilização mais usual se dá quando o paciente não é muito colaborativo, possui o número de dentes que não permite a ancoragem apropriada ou quando estes estão periodontalmente comprometidos.…”
Section: Revisão Da Literaturaunclassified